Trials and penal sanctions by non-state armed groups - Jöbstl, H (2023)
This thesis sets out the international legal framework applicable to the passing of penal sentences by armed groups during non-international armed conflicts and assesses the practical and normative challenges that it entails. It explains that international law neither explicitly prohibits nor explicitly permits the passing of penal sentences by armed groups and, therefore, that such groups enjoy a limited legal capacity to pass penal sentences. However, armed groups remain subject to exacting fair trial guarantees, most notably the requirement of a regularly constituted court providing all the necessary judicial guarantees recognised as indispensable. While not categorically outlawing the operation of courts and passing of penal sentences, these guarantees will often overstrain the factual capacities of armed groups in practice. Nevertheless, the thesis demonstrates that a downgrading of these guarantees is doctrinally problematic and normatively undesirable. Moreover, the thesis explains that international law, at present, does not place an obligation upon armed groups to use penal sanctions in order to enforce compliance with IHL. Neither the organisational threshold requirement under IHL, nor substantive customary law obligations or the doctrine of command responsibility can be interpreted to place such duty upon armed groups. Nevertheless, recent State practice indicates an increasing demand for accountability measures carried out by armed groups. While penal sanctions can play a role in meeting these demands in cases where the armed group in question operates a capable judicial system, alternative measures exist that allow for the implementation of accountability in situations where a fair trial cannot be provided.